The Effect of Advertising and Brand Image on Purchasing Decisions for Telkomsel Mobile Cards - Alif Nur Aliah; Asdar Djamereng; M. Mapparenta (Golden Ratio of Marketing and Applied Psychology of Business, 2021)
This study aims to determine the effect of advertising and brand image on purchasing decisions for Telkomsel mobile cards at SMA Negeri 3 Barru. This research was conducted using a quantitative approach and causal method. The quantitative approach is used to measure the relationship between the variables under study numerically, while the causal method helps in identifying the cause-and-effect between the variables. The research sample consisted of 100 students of SMA Negeri 3 Barru, who are potential consumers of Telkomsel mobile card products in the neighborhood. Research data were collected through two methods, namely observation and questionnaires filled out by SMA Negeri 3 Barru students. Observations were made to obtain information about student behavior related to cellular card purchasing decisions. In addition, questionnaires were used to collect data on students' perceptions of Telkomsel's advertisements and brand image as well as their purchasing decisions. After data analysis was carried out, it was found that the advertising and brand image variables had a significant influence on the purchasing decision variable. These results indicate that effective advertising and a positive brand image can increase the likelihood of SMA Negeri 3 Barru students to choose Telkomsel mobile cards as their choice. This study concludes that advertising and brand image play an important role in influencing purchasing decisions for Telkomsel cellular cards among SMA Negeri 3 Barru students. Therefore, telecommunications companies must continue to improve advertising strategies and build a strong brand image to support sales growth and maintain market share in the school environment and the local community. This study also provides insight for other researchers who are interested in digging deeper into the factors that influence purchasing decisions in an educational environment.